Enhancing discharge of spoil to mitigate disturbance induced by horizontal jet grouting in clayey soil: Theoretical model and application. (July 2019) - Wang, Zhi-Feng; Shen, Shui-Long; Modoni, Giuseppe
Abstract: The installation of jet grouting columns in fine-grained soils can cause significant disturbances to nearby structures, thereby undermining the reliability of this powerful technology. The high-pressure injection of large volumes of grouting materials coupled with the limited exhaust capacity of the boreholes often cause ground surface upheavals and lateral displacements. The problem appears particularly for horizontal columns injected at relatively shallow depths and in fine-grained soils. Systems employed to control the pressure in the injection cavity and fasten the spoil discharge represent an effective method to mitigate the ground disturbance. However, although the principle is well understood, there is no reliable analytical solution to predict ground movements caused by horizontal jet grouting and the resulting spoil discharge. This paper presents a simple calculation scheme to estimate ground movements induced by horizontal jet grouting. The method considers the jetting parameters, soil properties, and volume of discharged spoil. Further, a new equation is derived to calculate the radius of the plastic zone considering the discharged spoil. The proposed method is applied to interpret the observations obtained in two real case studies. The comparison of the calculation results and measured data confirms the effectiveness of the proposed method.